INOVASI PEMBUATAN ABON IKAN SEBAGAI SALAH SATU TEKNOLOGI PENGAWETAN IKAN - Kusumayanti, Heny; Astuti, Widi; Broto, RTD. Wisnu (Gema Teknologi, 2011)
Heny Kusumayanti, Widi Astuti, RTD. Wisnu Broto, in this paper explain that fish is one of the food-stuff which liked many and consumed by societies besides as commodity of export. In general fish quickly experience of the process of obsolence if compared to other food-stuff is so that required by  technology processing of fish to length then energy keep him, one of them is processing of fish become shredded fish. Region sub-district of Mangunharjo have big potency in fishery area, by halves societies work as farmer of fishpond. With existence of training to society about expected by society have adequate knowledge so that can exploit the area potency of to improve his life level. Activity method which used in this devotion is method deliver a lecture, method’s practice of concerning way making of shredded fish, and question and answer method. The result show that very enthusiastic society to making process  of shredded fish. Require to be done  by creativity and innovation in course of processing of shredded fish so that yielded product can certifiable and better. Keyword : Fish, Processing of fish, Shredded fish.